Exploiting RLL codes in visible light communication - Xuanxuan Lu; Li, Tiffany Jing (2016 IEEE/CIC International Conference on Communications in China (ICCC), 2016)
Visible light communication (VLC) provides the potential for high date rate communication at low power and cost, using LEDs. Run-length limited (RLL) codes are widely used in VLC to avoid long runs of 1's and 0's that could potentially cause the flicker and guarantee DC balance. However, the study of RLL codes in VLC is rather scant. We evaluate the dimming control and flicker analysis of three practical RLL codes: Manchester code, FM0/1 code and Miller code for their possible adoption in VLC in this paper. In addition to capturing the RLL functionality of the codes, we show that the FM0/1 code and Miller code can actually be treated as a trellis code with memory size 2. A modified BCJR algorithm for the trellis-based RLL codes is thus developed and a soft-iterative decoding algorithm is proposed for the forward error correction (convolutional) codes and RLL codes concatenated VLC system. The analysis show that the three RLL codes have advantages in different aspects. We also verify that the proposed iterative decoding scheme performs better than the existing ones in the numerical results.